Korelasi antara Keterampilan Penalaran Kritis dengan Hasil Belajar Kognitif Peserta Didik Kelas X - Tanti Difa Maulidta; Mimien Henie Irawati; Hari Santoso (SENTRI: Jurnal Riset Ilmiah, 2025)
This study was motivated by the importance of critical thinking skills in improving the quality of student learning outcomes, especially in an era of increasingly complex scientific and technological developments. Critical thinking skills are essential skills that influence the ability to understand information, solve problems, and make logical decisions. However, the actual conditions in Indonesia show that these skills are still relatively low, so it is necessary to examine the relationship between critical thinking skills and cognitive learning outcomes. This study used a quantitative approach with a correlational research design, involving 108 tenth-grade students at SMA Negeri 02 Batu in the 2025/2026 academic year. Data were collected through a critical reasoning skills test covering four indicators and a cognitive learning outcomes test based on Bloom's taxonomy (C1–C6). Data analysis used Pearson's correlation test and simple linear regression with the help of the SPSS 23 program. The results showed that students' critical reasoning skills were in the good category with an average score of 82.9, while cognitive learning outcomes were in the moderate category with an average score of 84.2. Pearson correlation test produced a value of r = 0.995 with a significance of < 0.001, indicating a very strong positive relationship between critical reasoning skills and cognitive learning outcomes. These findings confirm that improving critical reasoning skills contributes significantly to improving student learning outcomes. Therefore, the development of learning model that can stimulate critical thinking skills needs to be a concern in efforts to improve the quality of education.